2013
DOI: 10.1590/s1413-35552012005000058
|View full text |Cite
|
Sign up to set email alerts
|

Intra and inter-rater reliability of infrared image analysis of masticatory and upper trapezius muscles in women with and without temporomandibular disorder

Abstract: | Background: Infrared thermography is an aid tool that can be used to evaluate several pathologies given its efficiency in analyzing the distribution of skin surface temperature. Objectives: To propose two forms of infrared image analysis of the masticatory and upper trapezius muscles, and to determine the intra and inter-rater reliability of both forms of analysis. Method: Infrared images of masticatory and upper trapezius muscles of 64 female volunteers with and without temporomandibular disorder (TMD) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 41 publications
1
43
0
6
Order By: Relevance
“…43 Infrared thermography has been described in the literature as an assessment tool for individuals with different adverse health conditions, such as carpal tunnel syndrome, 44 breast cancer, 45 circulatory changes, 46 myofascial disorders 31 and TMD. 17,18 This painless, noninvasive, non-ionizing method does not require contact with the region being evaluated, thereby offering safety and comfort to the patient. 15 A number of studies have been conducted, but there is still no consensus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Infrared thermography has been described in the literature as an assessment tool for individuals with different adverse health conditions, such as carpal tunnel syndrome, 44 breast cancer, 45 circulatory changes, 46 myofascial disorders 31 and TMD. 17,18 This painless, noninvasive, non-ionizing method does not require contact with the region being evaluated, thereby offering safety and comfort to the patient. 15 A number of studies have been conducted, but there is still no consensus.…”
Section: Discussionmentioning
confidence: 99%
“…However, Costa, et al 18 evaluated the reliability of two forms of infrared image analysis of the masticatory muscles and upper trapezius muscle in women with and without TMD and found that both forms of analysis demonstrated excellent intra-examiner and inter-examiner reliability. The authors proposed both evaluation methods for these muscles, especially when the goal is to evaluate the effect of therapeutic resources.…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al (3) Intra and inter-rater reliability of infrared image analysis of masticatory and upper trapezius muscles in women with and without temporomandibular disorder.…”
Section: Author Title Methodsmentioning
confidence: 99%
“…(2) Computerized Infrared thermography is used as an effective tool for the diagnosis of various diseases because of its efficiency in the analysis of temperature distribution on the skin surface. (1)(2)(3)(4)(5)(6) There is an advantage use the fact that a procedure safe, noninvasive, that does not involve ionizing radiation and provides objective parameters for evaluation. (2,5,7) The human body exhibits a thermal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Pueden ser de gran utilidad la radiografía panorámica [64], la resonancia magnética [65,66], la tomografía axial computarizada [67], o herramientas más específicas como la imagenología infrarroja para determinar, mediante el comportamiento tér-mico, el estado de los músculos masticatorios [68].…”
Section: Ayudas Imagenológicasunclassified